Produção e partição de biomassa e de nutrientes e recomendação de fertilizantes para o Pinus taeda L. (Nutripinus) - Barros Filho, Nairam Félix de (2003)
The study was accomplished in close areas to the municipal districts of Arapoti and Curiúva, PR, belonging to the company INTERNATIONAL PAPER, in the period of November of 2002 to January of 2003. Stands, not thinned, of Pinus taeda L. in the ages of 2, 4, 6 and 8 years, were used. Three portions of 20 m x 30 m were demarcated in each stand. In each portion, there were chosen three trees: a first tree, with the medium diameter of the portion; the second tree, with the diameter corresponding to the less average a standard deviation; and the third tree, with diameter corresponding to the average one more deviation pattern. The measurement of these trees was made and abating them after taken the weight of needles, branches, peel and wood. Samples of each compartment of the tree were removed aiming at to establish the dry weight and the concentration of nutrients. In the medium trees of each portion, it was also collected the whole biomass of roots, being removed samples for the definition of the dry weight and a concentration of nutrient. Litterfall samples were collected in three points of the portion for also to proceed to the determination of the dry weight and a content of nutrient. The same sampling procedure was accomplished in the collection of soils for analysis of nutrient. It was verified that the relative contribution of needles and roots decreased, and of wood increased with the age of the trees. The nutrient concentration in the trees was below of the critical levels cited by literature. The trees with different DBH had not presented differences, between itself, to the nutients concentration, but it was detect a decreased of concentration with the age in all the components, except needles. The wood volume and the age had allowed esteem with precision the biomass of the components trees. The dry weight, content and nutrients efficiency equations, had presented high values of R². The system was shown efficient in the estimate of the contents of nutrients in the tree, as well as in the recommendation of fertilizers.